Broadband Second Harmonic Generation in a z-Cut Lithium Niobate on Insulator Waveguide Based on Type-I Modal Phase Matching - Changwen Wang; Haozong Zhong; Minghao Ning; Bin Fang; Lin Li; Ya Cheng (Photonics, 2023)
We numerically investigate a second harmonic generation (SHG) in a z-cut lithium niobate on insulator (LNOI) waveguide based on type-I mode phase matching (MPM) between two fundamental modes. A mode overlap factor that is close to unity is achieved and the normalized SHG efficiency reaches up to 72.1% W−1cm−2 at the telecommunication band, together with a large spectral tunability of 2.5 nm/K. Moreover, a bandwidth of about 100 nm for the broad SHG in a 5 mm-long LNOI ridge waveguide is demonstrated with this scheme. This stratagem will inspire new integrated nonlinear frequency conversion methods for versatile applications.